New tasks for EU-NATO cooperation: An inclusive EU defence policy requires close collaboration with NATO - Niklas Helwig (Stiftung Wissenschaft und Politik (SWP), 2018)
In recent years, difficult relations with Russia and the instability of the Southern Mediterranean have presented the EU and NATO with new challenges. They both put a stronger emphasis on countering hybrid threats, territorial defence and counterterrorism. In the course of this development, the EU and NATO have deepened their cooperation at staff level, while failing to harmonize their basic political and strategic objectives. EU Member States do not yet share a common understanding of the role of the EU and NATO in European defence. The EU could align the Permanent Structured Cooperation (PESCO), incorporated in the Union's Common Security and Defence Policy (CSDP), more closely with the objectives of NATO. This would be in line with the German idea of an inclusive EU defence policy.
Keywords: 320